Genetic Analysis of Yield and Quality Traits in Switchgrass Based on Population Crosses - Serge Edmé (MDPI AG, 2021)
Obtaining greater genetic gains, particularly for biomass yield, requires a good understanding of the gene action governing the inheritance of traits with economic importance in switchgrass (Panicum virgatum L.). Individual genotypes from three different accessions were crossed in single-pair matings with reciprocals to assess the relative importance of additive to nonadditive genetic variation and the potential of using inter-ecotypic crosses to improve dry matter yield (DMY), in vitro dry matter digestibility (IVDMD), lignin content (ADL and KL), and ethanol yield (ETOH). Crosses and four reference populations were planted in a randomized complete block design with eight replications of single family-rows plots, with five-plants each and 1 m spacings. A linear mixed model was applied as per the restricted maximum likelihood method, integrated with a pedigree tracing back to the original founders of these parental populations, and augmented with the designation of four genetic groups. Variation due to SCA (specific combining ability) was predominant for all traits, contributing from 20% to 57% of the total phenotypic variation and with Baker’s ratios (GCA/SCA) varying from 0.003 to 0.67. Heritability values calculated at the fullsib-family mean level were moderate to very high. Variation due to GCA (general combining ability) was detected with a lesser significance for DMY and ETOH. A reciprocal GCA effect was present in the form of maternal inheritance for DMY, suggesting the use of the highest biomass-yielding parent as female in inter-ecotypic breeding. Selecting and deploying fullsib families, deploying clonal hybrids, and adopting an introgression breeding approach are all possibilities available to switchgrass breeders to exploit the complementary genes from this germplasm and capitalize on the non-additive genetic variation present in these crosses.